Preserving Native Culture Through Traditional Costumes And Textiles: The Case Of The Rungus Community In Sabah, Malaysia - Romzi Ationg; Andreas Totu; Jane Wong Kon Ling; Rose Patsy Tibok; Jualang Gansau (2020)
A significant effect of the advent of the post-modern era is the waning interest among indigenous communities in many aspects of their own culture and traditions. The Rungus in Sabah, a sub-ethnic of the Kadazandusun or the Momogun community, is no exception to such phenomenon. For this reason, many, in particular the government and the Rungus of Sabah themselves should undertake efforts to preserve their traditions and ensure the richness and intricacies of the community’s heritage and culture remain relevant, known and promoted. The Rungus culture arguably could be sustained through the promotion of knowledge, awareness and appreciation of its traditional costumes and textiles. The issue however is to ascertain how this approach could be best effected. This qualitative study is aimed at determining how the Rungus culture in Sabah couldbe preserved and promoted through its traditional costumes and textiles. The findings of the study indicate visibility and consistent promotion as key to this preservation effort.